DAMPAK GADGET TERHADAP PERKEMBANGAN BAHASA ANAK USIA 3-6 TAHUN DI TK.KARTIKA TEBING TINGGI - Rebecca Octavia Sianturi; Jasper Simanjuntak (JURNAL TEMATIK, 2020)
The purpose of this study was to determine the impact of gadgets on language development of children aged 3-6 years in kindergarten. Kartika Tebing Tinggi. This type of research is a quantitative descriptive study. Data analysis techniques used were observation and interview sheets. The results of the study can be seen from the percentage of each child including the percentage of each child including KAZ of 46.87%, AV of 68.75%, SA 93.75%, AA 46.87%, KA 71.87%, GR 43.75%, RB 50%, 46.25%, F 40.62 %, RA 37.50%. Thus the overall average impact of gadgets on language development of children aged 3-6 years obtains a percentage of 54.06%. This can also be seen from the number of children who are considered poor, consisting of 7 out of 10 children with a percentage of 70%. As much as 1 child out of 10 reaches the criteria sufficient with a percentage of 10%, as many as 1 child out of 10 reaches the good criteria with a percentage of 10%, 1 child out of 10 achieves very good criteria with a percentage of 10. Because children are too focused on gadgets and parents do not limit the use of gadgets.